Writing the self: case studies in phenomenology and fiction - Venkatachalam, Shilpa (2007)
Writing the Self: Case Studies in Phenomenology and Fiction explores the way in which the notions of self, being and consciousness find expression in works of literary fiction and philosophical texts. It raises the question of whether there are paradigmatic features that are distinctive to philosophy and imaginative literature in their engagement with ontology. Whilst discussing various works of imaginative literature and philosophy, this thesis concentrates on aspects of Husserlian phenomenology and Martin Heidegger's Being and Time (1962) from the philosophical tradition and focuses on three selected works of post-1900 literary fiction: Joseph Conrad's Heart of Darkness (1902), Virginia Woolfs The Waves (1931), and Saul Bellow's Dangling Man (1944).